Effects on Clinical Outcomes of a 5-Year Surgical Safety Checklist Implementation Experience: A Large-scale Population-Based Difference-in-Differences Study. (20th July 2018) - Rodella, Stefania; Mall, Sabine; Marino, Massimiliano; Turci, Graziella; Gambale, Giorgio; Montella, Maria Teresa; Bonilauri, Stefano; Gelmini, Roberta; Zuin, Piera
The adoption of a surgical checklist is strongly recommended worldwide as an effective practice to improve patient safety; however, several studies have reported mixed results and a number of issues are still unresolved. The main objective of this study was to explore the impact of the first 5-year period of a surgical checklist-based intervention in a large regional health care system in Italy (4 500 000 inhabitants). We conducted a retrospective longitudinal study on 1 166 424 patients who underwent surgery in 48 public hospitals between 2006 and 2014. The adherence to the checklist was measured between 2011 and 2013 through a computerized database. The effects of the intervention were explored through multivariable logistic regression and difference-in-differences (DID) approaches, based on current administrative data sources. In-hospital and 30-days mortality, 30-days readmissions and length-of-stay (LOS) ⩾8 days were the observed outcomes. Adherence to the checklist showed marked variations across hospitals (0%-93.3%). A pre/post analysis detected statistically significant differences between surgical interventions performed in hospitals with higher adherence to the checklist (⩾75% of the surgeries) and those performed in other hospitals, as for the 30-days readmissions rate (odds ratio [OR]: 0.96; 95% confidence interval [CI]: 0.94-0.98) and LOS ⩾ 8 days rate (OR: 0.88; 95% CI: 0.87-0.89). These findings were confirmed after risk adjustment and DID analysis. No association was observed with mortality outcomes. On the whole, our study attained mixed results. Although a protective effect of the surgical checklist use could not be proved over the first 5 years of this regional implementation experience, our research offers some methodological insights for practical use in the evaluation process of large-scale implementation projects.